(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
A long-standing link exists between avant-garde and scientific cinema. In the 1920s, in fact, the former contributed to the construction of the latter: on the one hand, by its systematic inclusion in film clubs’ and film societies’ screening programs; on the other hand, by catalyzing the theoretical debate on the medium specificity because of the specific techniques it develops. Through the texts by philosophers, film makers and theorists of the time (Walter Benjamin, Germaine Dulac, Jean Epstein, Émile Vuillermoz, László Moholy-Nagy among others), this essay examines the role of microscope films in the construction of 1920s film theory, discussing several tropes and key concepts such as pure cinema, cinégraphie integrale, rhythm theory and optical “unconscious”.